Differences in Risk Perception Between the Construction and Agriculture Sectors: An Exploratory Study with a Focus on Carcinogenic Risk - Barattucci, Massimiliano; Ramaci, Tiziana; Matera, Serena; Vella, Francesca; Gallina, Valentino; Vitale, Ermanno (La Medicina del Lavoro, 2025)
Background: Risk perception is crucial in occupational health and safety, particularly in high-risk sectors like agriculture and construction. This study investigates the influence of personality traits, emotional states, and socio-demographic variables on perceived risks, explicitly focusing on carcinogenic exposure. The aim is to identify key factors shaping risk perception to inform safety interventions. Methods: Using a correlational research design, 91 Italian workers (49 from construction and 42 from agriculture) completed a comprehensive questionnaire assessing personality (Big Five model), emotional state, self-perceived safety knowledge, and risk perception across 14 dimensions. Statistical analyses included correlations, ANOVA, and regression models to explore relationships between variables. Results: Open-mindedness, emotional stability and extraversion were inversely related to perceived risk levels, while conscientiousness and friendliness correlated positively. Workers in agriculture reported higher awareness of carcinogenic risks than construction workers, though no significant differences emerged in perceived risk levels. Negative emotional states predicted higher risk perception, while self-perceived safety knowledge had only minor correlations with specific risk dimensions. Gender, age, and service length did not significantly influence risk perception. Conclusion: Personality traits, particularly openness and emotional stability, strongly influence risk perception, highlighting the importance of considering individual psychological profiles in occupational safety interventions. Although emotional state plays a notable role, self-perceived safety knowledge showed limited impact, suggesting a need for targeted education.